(untitled) (Research, Society and Development, 2020)
This article aims to identify the profile of accounting professionals in accounting offices in the city of Marabá-PA. It is an exploratory and descriptive research with a quantitative approach. The profile of the accounting professional has been undergoing changes, due to the new digital accounting record platforms and a charge for a more active participation in decision making. The sample consisted of 20 questionnaires, distributed in 20 accounting offices (Marabá-PA). The research was carried out from 15 to 23 October 2019 and subsequent analysis, with the display of graphs and tables of the researched data. The results enabled the identification of factors that influence the choice of offices in the hiring phase of accountants, the identification of the candidates’ home university, the difficulties of some accountants with technology, among others. Among the researched data, it is still possible to identify the predominance of males in accounting offices, in an age range of up to 34 years, in addition to clearly demonstrating a new professional accounting profile compared to the old one, where intellectual capital is valued every day. . And so it is concluded that the vacancies are occupied by accountants attentive to the needs of companies, capable of providing objective and reliable information and solutions for their management and exercising their profession with ethics and responsibility.